A Child with Interstitial Granulomatous Dermatitis and Juvenile Idiopathic Arthritis. Issue 6 (5th June 2013) - Moon, Hye‐Rim; Lee, Ji‐Hyun; Won, Chong Hyun; Chang, Sung Eun; Lee, Mi Woo; Choi, Jee Ho; Moon, Kee Chan
Abstract We describe a case of interstitial granulomatous dermatitis (IGD) with juvenile idiopathic arthritis (JIA) in an 11‐year‐old girl. She complained of erythematous plaques on her thighs and polyarthritis for 1 year. Histopathologic examination revealed the features of IGD. This case indicates that IGD with arthritis can occur in children and should be considered in the differential diagnosis of cutaneous lesions associated with arthritis in children.